Efficacy of the FIFA cooling break heat policy during an intermittent treadmill football simulation in hot conditions in trained males - Brown, H. A.; Chalmers, S.; Topham, T. H.; Clark, B.; Jowett, A.; Meyer, T.; Jay, O.; Périard, J. D. (British Journal of Sports Medicine, 2024)
Objective To evaluate the efficacy of the Fédération Internationale de Football Association (FIFA) cooling break policy against alternative cooling configurations in attenuating thermal strain during simulated football in the heat.